Electromagnetic induction measurements with the vertically oriented dipole of the CMD Mini Explorer (32 cm transmitter-receiver spacing) taken in June 2023 in the Lower Havel Inner Delta near Lake Gülpe, Brandenburg (Germany) - Marco Pohle; Matteo Bauckholt; Ulrike Werban (PANGAEA, 2025)
Electromagnetic induction (EMI) was measured with a CMD-Mini Explorer (GF Instruments s.r.o., Brno, Czech Republic) in June 2023. We used the vertical dipole (VDP) at coil spacings of 0.32 m (VDP1), 0.71 m (VDP2) and 1.18 m (VDP3), archieving effective penetration depths of 0.5 m (VDP1), 1.0 m (VDP2) and 1.8 m (VDP3). According to the manufacturer, 70% of the signal originate from above these depths. The EMI sensors measure the apparent electrical conductivity (ECa, in mS/m). Measurements were taken by carrying the instrument about 0.2 m above ground while being directly connected to D-GPS (Leica GPS1200) for positioning. The acquisition rate was five measurements per second. Data quality was checked by measuring a reference line before and after each measurement. The area investigated by EMI in June 2023 is located to the north and northeast of the Gülpe research station. It has a total area of 12.3 ha. The reference line was located in the southern part of the study area. No drift correction had to be applied due to good data quality. Reference lines and single outliers were removed. The data set contains the EMI data with an intercoil spacing of 0.32 m.
In: Köhler, Anne; Pohle, Marco; Bauckholt, Matteo; Birnstengel, Susann; Kaniecki, Marie; Schneider, Birgit; Werban, Ulrike; Zielhofer, Christoph (2025): Geophysical, Sedimentological and Geochemical Data from the Lower Havel Inner Delta (Gülpe Island), Brandenburg (Germany) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.983208